High-level recombinant production of squalene using selected Saccharomyces cerevisiae strains. (1st April 2018) - Han, Jong Yun; Seo, Sung Hwa; Song, Jae Myeong; Lee, Hongweon; Choi, Eui-Sung
Abstract: For recombinant production of squalene, which is a triterpenoid compound with increasing industrial applications, in microorganisms generally recognized as safe, we screened Saccharomyces cerevisiae strains to determine their suitability. A strong strain dependence was observed in squalene productivity among Saccharomyces cerevisiae strains upon overexpression of genes important for isoprenoid biosynthesis. In particular, a high level of squalene production (400 ± 45 mg/L) was obtained in shake flasks with the Y2805 strain overexpressing genes encoding a bacterial farnesyl diphosphate synthase ( ispA ) and a truncated form of hydroxyl-3-methylglutaryl-CoA reductase ( tHMG1 ). Partial inhibition of squalene epoxidase by terbinafine further increased squalene production by up to 1.9-fold (756 ± 36 mg/L). Furthermore, squalene production of 2011 ± 75 or 1026 ± 37 mg/L was obtained from 5-L fed-batch fermentations in the presence or absence of terbinafine supplementation, respectively. These results suggest that the Y2805 strain has potential as a new alternative source of squalene production.